Creative class as a determinant of economic development: empirical considerations for North Rhine-Westphalian regions based on time series analysis - Rüdiger Hamm (European Regional Science Association (ERSA), 2011)
Since some years Richard Florida's ideas on the creative class have attracted a great deal of theoretical and empirical attention. One part of his theory says that the "creative class" - people with highly creative and innovative abilities - are the driving force of regional economic development. The proposed paper empirically deals with this relationship; it describes some empirical research done for the regions (NUTS 3) of Northrhine-Westphalia which is a federal state of Germany. The regional distribution of creative people in Northrhine-Westphalia is described in the first chapter. The second chapter analyzes the relationship between the creative class and regional economic development. But unlike most other empirical research on that topic time series data for the period between 1999 and 2008 is used as a starting point. The time series analysis is completed by some additional cross-section regressions. The often mentioned criticism on Florida's theory is accounted for by considering educational (i.e. human capital) versus occupational (i.e. the creative class) data for these regressions. The empirical results suggest that Florida's thesis only holds true for a part of the Northrhine-Westphalian regions but not for the other part. Therefore cluster analysis is used to find out whether there are other conditions to be fulfilled by a region that a "creative-class-effect" on regional economic development arises. The main results of this cluster analysis will be presented in the third chapter. The paper ends with a summary and some concluding remarks.
Keywords: 330